2002
DOI: 10.1021/bi0268706
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Structure and Catalysis for Ketoreductase Domains in Modular Polyketide Synthases

Abstract: A putative catalytic triad consisting of tyrosine, serine, and lysine residues was identified in the ketoreductase (KR) domains of modular polyketide synthases (PKSs) based on homology modeling to the short chain dehydrogenase/reductase (SDR) superfamily of enzymes. This was tested by constructing point mutations for each of these three amino acid residues in the KR domain of module 6 of the 6-deoxyerythronolide B synthase (DEBS) and determining the effect on ketoreduction. Experiments conducted in vitro with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
284
1
16

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(312 citation statements)
references
References 21 publications
11
284
1
16
Order By: Relevance
“…Reductase-active KR domains can be inferred by the presence of three diagnostic regions for binding NADPH: a GxGxxG motif, a swap linker and a WGxW motif (Garg et al 2014). Also the presence of the catalytic triad lysine, serine and tyrosine should also be present in active KR domains (Reid et al 2003). All of the KR domains found in the chaxalactin PKS possess all of the described motifs and are expected to be active, consistent with the structures of chaxalactins A-C.…”
Section: The Chaxamycin Biosynthesis Gene Clustersupporting
confidence: 65%
See 1 more Smart Citation
“…Reductase-active KR domains can be inferred by the presence of three diagnostic regions for binding NADPH: a GxGxxG motif, a swap linker and a WGxW motif (Garg et al 2014). Also the presence of the catalytic triad lysine, serine and tyrosine should also be present in active KR domains (Reid et al 2003). All of the KR domains found in the chaxalactin PKS possess all of the described motifs and are expected to be active, consistent with the structures of chaxalactins A-C.…”
Section: The Chaxamycin Biosynthesis Gene Clustersupporting
confidence: 65%
“…Thus the export of this lasso peptide is presumably mediated by a non-specific efflux pump present in many streptomycetes (Gomez-Escribano et al, unpublished results). The amino acid sequence of the predicted mature form of the lasso peptide of lp2 appears thus far to be novel and could not be detected in the draft genome sequence of strain C58 (GomezEscribano et al 2015;Razmilic 2017); lp2 is currently under study (Gomez-Escribano et al, unpublished results).…”
Section: Three Lasso Peptide Biosynthesis Gene Clustersmentioning
confidence: 99%
“…Interestingly, both of these split modules may introduce an unusual cis olefin into the growing chain. Earlier work on the stereochemistry of the KR reaction in polyketide biosynthesis linked the presence/absence of a conserved aspartate residue in the KR domain with the stereochemical outcome of the subsequent dehydration reaction (16)(17)(18). Indeed, the three modules in the PksX synthase that generate a cis double bond lack this conserved aspartate in the KR domain (i.e., PksJ-KR2, PksL-KR2, and PksM-KR1).…”
Section: Resultsmentioning
confidence: 99%
“…However, since all modules contain KR domain, certain contradiction appeared between the gene structure and the chemical structure. Some inactive KR domains have been reported to lack the active site motif, GXGXXGXXXA for NADP-binding or the catalytic triad, Lys, Ser and Tyr in the active site [8]. However, in the case of hls KR, all the important amino acid residues appeared to be conserved in all KR.…”
Section: Pks Genesmentioning
confidence: 99%
“…Usually, most of the double bond geometry found in polyketide chains is E-configuration. It has been suggested that the stereochemistry of b-hydroxyl group derived from KR domain might control the double bond geometry in DH domain [8]. An Asp residue of KR domain was proposed to be an important residue for determining the stereospecificity.…”
Section: Pks Genesmentioning
confidence: 99%